Assessment of the Succes Implementing Mobile Banking at East Nusa Tenggara Bank: Penilaian Keberhasilan Penerapan Mobile Banking pada Bank Nusa Tenggara Timur - Oktariyana, Made Denny; Kadek Bagiana (Fakultas Dharma Duta UHN IGB Sugriwa Denpasar, 2023)
This research aims to determine the influence of Information Quality, Information System Quality, Service Quality, on User Satisfaction. This research uses a quantitative approach, this research was conducted at Bank Nusa Tenggara Timur (NTT). Bank NTT launched a Mobile Banking application (B'Pung Mobile) but does not yet have permission from Bank Indonesia so a system analysis needs to be carried out regarding the quality provided. This research refers to Financial Services Authority (OJK) regulations regarding the Crime of Money Laundering (TPPU), the Crime of Terrorism Financing (TPPT), and the Funding for the Proliferation of Weapons of Mass Destruction (PPSPM). The sampling method uses the incidental sampling method. The sample in this research is Bank NTT customers who use Mobile Banking. The total sample in this study was 200 samples. This research data was collected using a questionnaire which was then processed using multiple linear regression analysis tests with the help of SPSS version 24. The results of the research state that (1) Information Quality partially has a positive and significant effect on Mobile Banking User Satisfaction at Bank NTT. (2) Information System Quality partially has a positive and significant effect on Mobile Banking User Satisfaction at Bank NTT. (3) Service Quality partially has a positive and insignificant effect on Mobile Banking User Satisfaction at Bank NTT.